2014
DOI: 10.1016/j.kjms.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Survival of motor neuron protein downregulates miR‐9 expression in patients with spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a lethal hereditary disease caused by homozygous absence of the survival of the motor neuron (SMN) 1 gene (SMN1), and it is the leading genetic cause of infant mortality. The severity of SMA is directly correlated with SMN protein levels in affected patients; however, the cellular regulatory mechanisms for SMN protein expression are not completely understood. In this study, we investigated the regulatory effects between SMN expression and miR-9a, a downstream noncoding small RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…More studies will be needed to confirm that miR-2 and miR-128 are orthologs. Regardless, the results presented here, in conjunction with previous research, suggest that overall miRNA misregulation contributes to neuronal defects when SMN levels decrease (Haramati et al, 2010; Kye et al, 2014; Valsecchi et al, 2015; Wang et al, 2014; Wertz et al, 2016). …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…More studies will be needed to confirm that miR-2 and miR-128 are orthologs. Regardless, the results presented here, in conjunction with previous research, suggest that overall miRNA misregulation contributes to neuronal defects when SMN levels decrease (Haramati et al, 2010; Kye et al, 2014; Valsecchi et al, 2015; Wang et al, 2014; Wertz et al, 2016). …”
Section: Discussionsupporting
confidence: 77%
“…Disruption of the miRNA pathway in spinal MNs leads to severe degeneration (Haramati et al, 2010). SMN loss alters levels and/or activity of specific miRNAs (Haramati et al, 2010; Kye et al, 2014; Valsecchi et al, 2015; Wang et al, 2014), but the cellular mechanisms leading to altered miRNA expression and/or function are unknown. The RNA helicase Gemin3 associates with both SMN and RNA-induced silencing complex components (Charroux et al, 1999; Höck et al, 2007; Hutvágner and Zamore, 2002; Meister et al, 2005; Mourelatos et al, 2002; Murashov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…19 The conversely increased level of miR-9 in TA muscles is consistent with a report that miR-9 is upregulated in fibroblasts with SMN protein deficiency. 40 miR-132 also has contrary abundance in spinal cord and skeletal muscle. miR-132 plays an important role in neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mice lacking the miRNA-processing enzyme Dicer selectively in motor neurons display hallmarks of SMA (Haramati et al, 2010). Also, SMN protein has been shown to alter miRNA expression and distribution in neurons (Kye et al, 2014; Wang et al, 2014). Specifically, miR-183 is increased in neurites of SMN-deficient neurons.…”
Section: Mirnas In Motor Neuron Diseases: Dysregulation Diagnosis Anmentioning
confidence: 99%
“…SMN protein also down-regulates the expression of miR-9a. Interestingly, miR-9a levels have shown a positive correlation with SMA severity (Wang et al, 2014). A more recent study has shown that miR-431, involved in motor neuron neurite length, also plays a role in the SMA motor neuron phenotype.…”
Section: Mirnas In Motor Neuron Diseases: Dysregulation Diagnosis Anmentioning
confidence: 99%